Bus scheduling algorithm for UiTM Shah Alam / Muhd Hisyam Nursalam Ahmad Pauzi - Ahmad Pauzi, Muhd Hisyam Nursalam (2017)
Bus is one of the main public transportation use by most students in UiTM Shah Alam. The public bus provided the university is one of the benefits provided for the student in the campus to reach classes. Although the students are able to benefits from this public transportation, there are also a few downside in the service of the public bus. One of the main reasons is the bus arrival time is unknown to their student as there is timetables provided on the arrival time of the bus.Due to this limitation, the student of UiTM Shah Alam are most likely to waste most of their precious time which can be use to attend others important activities to wait for the bus. In order to avoid this kind of problem from occurring, a system is proposed which is to create a scheduling algorithm to calculate the arrival time of the bus which is then provide the students with the timetables. Dijkstra algorithm is one of the technique use in calculating the arrival time with high accuracy. In realizing this project, Waterfall Methodology Software Development is utilize in managing the project.lt is a methodology which focus on the quality of the requirement and design which is the most suitable for this project that emphasize on the accuracy of time. With the completion of this project, it is hope to provide the students with a timetable that shows the arrival time of the bus which can gives more benefits to the students.